Bulk Flow Behaviour of a Two-Stage Impedance Pump - Lee, Vincent; Gan, H.S.; Abakr, Y.; Woo, K. (Newswood Ltd, 2014)
Impedance pump is a type of valveless pumping mechanism, in which the design consists only elastic tubing joined with tubes of different impedances. By inducing a periodic asymmetrical compression on the elastic tube, thus will eventually produce a unidirectional flow within the system. Numerous works, computational and experimental, had been performed in past decades to explore this phenomenon and to further understand its characteristics. However, not many works were found in multi-stage valveless impedance pumping. The aim of this work is to have an insight on the bulk flow behaviour of an open-loop two-stage impedance pumping system at resonance. This paper emphasizes on the experimental study of the bulk flow behaviour with a partial of numerical study. Characteristics of a two-stage impedance pumping system with respect to its governing parameters were evaluated and results obtained were very significant.